2009
DOI: 10.1161/circoutcomes.109.848473
|View full text |Cite
|
Sign up to set email alerts
|

Number Needed to Treat With Rosuvastatin to Prevent First Cardiovascular Events and Death Among Men and Women With Low Low-Density Lipoprotein Cholesterol and Elevated High-Sensitivity C-Reactive Protein

Abstract: for the JUPITER Study GroupBackground-As recently demonstrated, random allocation to rosuvastatin results in large relative risk reductions for first cardiovascular events among apparently healthy men and women with low levels of low-density lipoprotein cholesterol but elevated levels of high-sensitivity C-reactive protein. However, whether the absolute risk reduction among such individuals justifies wide application of statin therapy in primary prevention is a controversial issue with broad policy and public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(78 citation statements)
references
References 24 publications
4
72
0
2
Order By: Relevance
“…Finally, the requested data on numbers needed to treat have previously been published 4 and again indicate that the strategy of using statin therapy among individuals with elevated high-sensitivity C-reactive protein is at least as effective as the strategy of using statin therapy only among those with hyperlipidemia. …”
mentioning
confidence: 99%
“…Finally, the requested data on numbers needed to treat have previously been published 4 and again indicate that the strategy of using statin therapy among individuals with elevated high-sensitivity C-reactive protein is at least as effective as the strategy of using statin therapy only among those with hyperlipidemia. …”
mentioning
confidence: 99%
“…This seems a reasonable threshold when compared with the thresholds of 7.5% to 10% that are applied in current clinical guidelines for primary prevention 2,3,29 and even more when compared with the secondary prevention setting, in which NNTs are clearly lower with average 5-year NNTs ranging from 15 to 33, corresponding with 10-year NNTs of 8 to 17. 37 For preventive therapies that are associated with considerably higher NNTs, such as blood-pressure-lowering therapy (5-year NNTs between 80 and 160, 37 corresponding with 10-year NNTs between 40 and 80), previous studies have shown that applying a prediction model may similarly result in higher net benefit compared with a strategy in which all patients are treated. 38,39 Importantly, in patients at relatively high risk of cardiovascular events, the net benefit of a prediction-based treatment strategy will be comparable to a strategy in which all patients are treated because high-risk patients are likely to exceed the treatment threshold and therefore all will be treated in both scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 It should be noted that although C-reactive protein has been demonstrated to be an independent predictor of cardiovascular risk, it is not strongly related to the relative risk reduction of statins, although the evidence is not entirely consistent. 13,15,16 Thus, there is strong scientific evidence that LDL is not a very useful factor in determining who is at risk for cardiovascular disease or how much that risk will be reduced by a statin (Table).…”
Section: There Is No Scientific Basis To Support Treating To Ldl Targetsmentioning
confidence: 99%